1975
DOI: 10.1161/01.cir.51.6.1085
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory changes of the distal coronary vascular bed during progressive coronary constriction.

Abstract: SUMMARYThe degree and effectiveness of compensatory changes in the distal coronary vascular bed during progressive proximal coronary stenosis have not been described. In this study, coronary vascular bed resistance and pressure gradient-flow relationships were determined for 157 Neither the flow transducer nor circumflex catheters affected maximum coronary flows or induced significant pressure gradients. This observation was repeatedly confirmed by recording maximal flows before and after insertion of the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(73 citation statements)
references
References 24 publications
4
69
0
Order By: Relevance
“…(It should be emphasized that the pressure axis intercepts and peripheral coronary pressures should be similar, as shown in Figure 3, because the pressure during complete coronary occlusion is indeed the lowest point on the pressure-flow curve.) In the isolated circumflex coronary artery, pressures of 14-30 mm Hg have been reported for peripheral coronary pressures (Mosher et al, 1964;Fam and McGregor, 1964;Elliot et al, 1968;Fam and McGregor, 1969;Elliot et al, 1974;Gould et al, 1975) and for pressure axis intercepts (Bellamy, 1978;Verrier et al, 1980;Vlahakes et al, 1982;Dole and Bishop, 1982). On the other hand, in the left main coronary artery, Eng et al (1982) found an average pressure axis intercept of 10.7 ± 2.4 mm Hg, close to our mean value of 8.1 mm Hg; had they used curvilinear rather than linear extrapolation, their intercept would have been even lower.…”
Section: Effects Of Interarterial Pressure Gradientssupporting
confidence: 81%
“…(It should be emphasized that the pressure axis intercepts and peripheral coronary pressures should be similar, as shown in Figure 3, because the pressure during complete coronary occlusion is indeed the lowest point on the pressure-flow curve.) In the isolated circumflex coronary artery, pressures of 14-30 mm Hg have been reported for peripheral coronary pressures (Mosher et al, 1964;Fam and McGregor, 1964;Elliot et al, 1968;Fam and McGregor, 1969;Elliot et al, 1974;Gould et al, 1975) and for pressure axis intercepts (Bellamy, 1978;Verrier et al, 1980;Vlahakes et al, 1982;Dole and Bishop, 1982). On the other hand, in the left main coronary artery, Eng et al (1982) found an average pressure axis intercept of 10.7 ± 2.4 mm Hg, close to our mean value of 8.1 mm Hg; had they used curvilinear rather than linear extrapolation, their intercept would have been even lower.…”
Section: Effects Of Interarterial Pressure Gradientssupporting
confidence: 81%
“…Such findings may agree with the Hagen-Poiseuille law, which denotes the resistance to flow in a tube interacting with serial branches along its length. 27 According to this, the intracoronary resistance depends on the coronary flow velocity and inversely on the fourth power of the vessel diameter, while interacting with branches along its length, that causes flow shunting from the parent artery and the longitudinal perfusion or MBF gradient. As it was observed, the extent of the longitudinal MBF difference was related to the severity of CAC, which has been shown to reflect overall CAD burden, 26 and also to the increase in hyperemic MBF or microvascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Group 1 patients (14 men, one woman; age, 55±7 years; range, years) were selected for the study because of the following characteristics: 1) isolated, proximal left anterior descending coronary artery stenosis, 2) stable angina pectoris associated with objective signs of myocardial ischemia on effort or during dipyridamole echocardiography test, 3) no clinical or ECG evidence of previous myocardial infarction, 4) no history of hypertension or left ventricular hypertrophy (septal or posterior wall < 12 mm at echocardiography), 5) no conduction abnormalities, and 6) exclusion of other cardiac disorders.…”
Section: Methods Patientsmentioning
confidence: 99%